Lumped negative stiffness damper for absorption of flexural waves in a rod. (9th March 2017) - Balch, Samuel P; Lakes, Roderic S
Abstract: A damper based on negative stiffness from column tilt buckling was used to achieve enhanced mechanical damping of bending vibration of a rod. Damping increased by a factor of three, via a damper column that was only about 0.2% of the mass of the aluminum alloy rod to be damped.